Macroeconomic Effects of Pension Reform in Russia - Hauner, David (IMF Working Papers; Working Paper ;, 2008)
Putting the pension system on a sustainable footing arguably remains the biggest challenge in Russia's economic policies. The debate about the policy options was hitherto constrained by the absence of general equilibrium analysis. This paper fills this gap by simulating their macroeconomic effects in a DSGE model calibrated to Russia's economy-the first of its kind to the best of our knowledge. The results suggest that a minimum benefit level in the public system should optimally be financed through lower government consumption, while higher taxation of labor and capital should be avoided. Reducing public investment spending is superior to increasing consumption taxes unless investment generates high rates of return.